ZTA ceramic material as well as preparation method and application thereof
By using ZTA ceramic materials, the crystal transformation of zirconia and the spatial residue of plate-like corundum are used to solve the problems of fracture risk and high cost of existing ceramic materials at high temperatures, achieving high strength, high toughness and superior thermal shock resistance. High-performance ceramic materials meet the needs of the photovoltaic field.
Patent Information
- Application Number
- CN202411494695.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-21
AI Technical Summary
Existing ceramic materials have stresses caused by thermal expansion or contraction at high temperatures, which are prone to risk of fracture and are costly, making it difficult to meet the demand for high-temperature materials in the photovoltaic field.
ZTA ceramic material is used. Its powder raw materials include zirconia, tabular corundum and inorganic oxide. It is prepared through spray granulation and sintering processes. The crystal form transformation of zirconia and the spatial residual of tabular corundum are used to improve the heat resistance of the ceramic material. Shock and high temperature performance.
ZTA ceramic materials with high strength, high toughness and superior thermal shock resistance at high temperatures have been realized, reducing preparation costs and meeting the demand for ceramic materials in the photovoltaic field.
Smart Images

Figure CN119330690A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaic materials and relates to an alumina ceramic material, in particular to a ZTA ceramic material and a preparation method and application thereof. Background Art
[0002] The preparation process of photovoltaic silicon wafers requires high temperatures and rapid temperature rise and fall, which places high demands on high-temperature resistant inorganic materials.
[0003] Ceramics in the prior art include alumina ceramics, mullite ceramics and carbide ceramics. However, the grains of alumina ceramics are tightly bonded during the preparation process. Although they have good mechanical properties at room temperature, they expand or contract rapidly when the temperature is rapidly increased or decreased, resulting in the grain boundaries between the grains being unable to meet the spatial expansion requirements, causing stress in the alumina ceramics and a risk of fracture during use. Mullite ceramics use large-sized grains to increase the space between the grains to cope with the thermal expansion problem caused by temperature increase or decrease, but the degree of grain bonding is poor, and the mechanical properties at both room and high temperatures cannot meet the requirements of high-load work. Silicon carbide ceramics have excellent performance at high temperatures, but their cost is high, more than ten times that of general high-temperature materials, and they cannot be used in large quantities.
[0004] CN117776751A discloses a method for preparing a highly wear-resistant ZTA ceramic material, which uses zirconium oxide and aluminum oxide as the main crystal phases and nano-carbon fibers as toughening agents, but it does not involve improvements in thermal shock resistance; CN117602956A discloses an aluminum oxide photovoltaic insulating ceramic, whose raw materials include aluminum oxide, single-walled carbon nanotubes, silicon nitride and silicon dioxide, but it also does not involve improvements in thermal shock resistance. CN118026658A discloses a low-heat storage mullite sagger of high-purity aluminum oxide powder and its preparation method, but the mechanical properties and thermal shock resistance of the mullite material are poor.
[0005] Therefore, how to provide a ZTA ceramic material with low cost, high strength, high toughness and excellent thermal shock resistance at high temperature and its preparation method and application is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0006] The object of the present invention is to provide a ZTA ceramic material and a preparation method and application thereof. The ZTA (zirconia toughened alumina) ceramic material has a low preparation cost and has high strength, high toughness and excellent thermal shock resistance at high temperatures, which can meet the increasing demand for ceramic materials in the photovoltaic field.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a ZTA ceramic material. In terms of mass percentage, the powder raw materials of the ZTA ceramic material include 5wt% to 69wt% of zirconium oxide, 5wt% to 21wt% of plate-like corundum, 3wt% to 5wt% of inorganic oxides and 21wt% to 79wt% of aluminum oxide.
[0009] Zirconia has the property of reversible crystal transformation at high temperature. During the preparation process of ZTA ceramic materials, the crystal transformation leads to the generation of space inside the ZTA ceramic materials. This part of the space can be used for thermal expansion of grains, thereby enhancing the thermal shock resistance of ZTA ceramic materials. Under high temperature conditions, monoclinic zirconia transforms into a tetragonal phase with better stability, thereby enhancing the high temperature performance of ZTA ceramic materials and making up for the defect that the performance of ceramic materials decreases at high temperatures. Tabular corundum can leave a large amount of space vacancies during the preparation process of ZTA ceramic materials, thereby further improving the thermal shock resistance of ceramic materials and making up for the defect that the price of zirconia is too high. Moreover, the use of inorganic oxides plays a role in inhibiting grain growth and can reduce the firing temperature, so that the ceramic materials meet the various requirements of photovoltaic devices.
[0010] In the powder raw material of ZTA described in the present invention, the mass percentage of zirconium oxide is 5wt% to 69wt%, for example, it can be 5wt%, 10wt%, 30wt%, 40wt%, 50wt%, 60wt% or 69wt%, but is not limited to the listed values, and the remaining values not listed in the numerical range are also applicable.
[0011] The plate-like corundum in the present invention can further improve the thermal shock resistance of the ZTA ceramic material. When the amount of the plate-like corundum is too small, the thermal shock resistance of the ZTA ceramic material is not significantly improved; and when the amount of the plate-like corundum is too large, it will have an adverse effect on the mechanical properties of the ZTA ceramic material. Therefore, in the powder raw material of ZTA described in the present invention, the mass percentage of the plate-like corundum is 5wt% to 21wt%, for example, it can be 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt% or 21wt%, but is not limited to the listed values, and the remaining values not listed in the numerical range are also applicable.
[0012] The appropriate inorganic oxide content can reduce the preparation cost and ensure the thermal shock resistance of ZTA ceramic materials.
[0013] In the powder raw material of ZTA described in the present invention, the mass percentage of inorganic oxide is 3wt% to 5wt%, for example, it can be 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] The appropriate aspect ratio of the plate-like corundum can ensure the thermal shock resistance of the obtained ZTA ceramic material. As a preferred technical solution of the present invention, as a preferred technical solution, the maximum length of the plate-like corundum is the length, the thickness of the plate-like corundum is the height, and the aspect ratio of the plate-like corundum is 8:1 to 12:1, for example, it can be 8:1, 9:1, 10:1, 11:1 or 12:1, but is not limited to the listed values, and the remaining values not listed in the numerical range are also applicable.
[0015] Preferably, the average particle size of the plate-like corundum is 0.8 μm to 1.2 μm, for example, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm or 1.2 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0016] Preferably, the zirconium oxide includes monoclinic zirconium oxide and yttrium-stabilized tetragonal zirconium oxide.
[0017] The yttrium-stabilized tetragonal zirconia described in the present invention is composed of zirconium oxide and yttrium oxide, and the total molar percentage of zirconium oxide and yttrium oxide is 100%, wherein the molar percentage of yttrium oxide is 3% to 8%, for example, it can be 3%, 4%, 5%, 6% or 8%, but is not limited to the listed values, and the remaining unlisted values within the numerical range are also applicable, preferably 3% to 5%.
[0018] Preferably, in the raw materials for preparing the ZTA ceramic material, the amount of monoclinic zirconium oxide is lower than the amount of yttrium-stabilized tetragonal zirconia.
[0019] In the present invention, the use of monoclinic zirconia can ensure the flexural strength and thermal shock resistance of the ZTA ceramic material, but pure monoclinic zirconia is unstable. When all zirconium oxide is monoclinic zirconia, it is not conducive to further improving the performance of the ceramic material. In order to balance the mechanical properties and thermal shock resistance of the obtained ceramic material, it is preferred to make the amount of monoclinic zirconia lower than the amount of yttrium-stabilized tetragonal zirconia.
[0020] Preferably, the powder raw material of the ZTA ceramic material includes, by mass percentage, 5wt% to 39wt% of monoclinic zirconium oxide and 5wt% to 40wt% of yttrium-stabilized tetragonal zirconia.
[0021] The powder raw material of the ZTA ceramic material provided by the present invention includes 5wt% to 69wt% of zirconium oxide, and the zirconium oxide includes a combination of monoclinic zirconium oxide and yttrium-stabilized tetragonal zirconia. Since the amount of monoclinic zirconium oxide in the preferred embodiment is lower than the amount of yttrium-stabilized tetragonal zirconia, as a further preferred technical scheme, the mass percentage of monoclinic zirconium oxide is 5wt% to 39wt% of the powder raw material, for example, it can be 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt% or 39wt%, but is not limited to the listed values, and the remaining values not listed in the numerical range are also applicable; the yttrium-stabilized tetragonal zirconia is 5wt% to 40wt% of the powder raw material, for example, it can be 5wt%, 11wt%, 16wt%, 21wt%, 27wt%, 31wt%, 36wt% or 40wt%, but is not limited to the listed values, and the remaining values not listed in the numerical range are also applicable.
[0022] Preferably, the average particle size of the zirconium oxide is 0.8 μm to 1.2 μm, for example, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm or 1.2 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Preferably, the inorganic oxide comprises silicon oxide (SiO 2 ), magnesium oxide (MgO), yttrium oxide (Y 2 O 3 ) or calcium oxide (CaO) or a combination of at least two of them, preferably a combination of silicon oxide, magnesium oxide, yttrium oxide and calcium oxide.
[0024] Preferably, the mass ratio of the silicon oxide to the magnesium oxide is 1:1 to 1:3, for example, 1:1, 1:2 or 1:3, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] The mass ratio of the silicon oxide to the yttrium oxide is 1:1 to 1:3, for example, 1:1, 1:2 or 1:3, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] The mass ratio of silicon oxide to calcium oxide is 1:1 to 1:3, for example, 1:1, 1:2 or 1:3, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] In a second aspect, the present invention provides a method for preparing the ZTA ceramic material as described in the first aspect, the preparation method comprising the following steps:
[0028] The powder raw material, binder, dispersant and solvent are uniformly mixed, the obtained slurry is sprayed and granulated, and then formed and sintered to obtain the ZTA ceramic material.
[0029] Preferably, the mixing method includes ball milling mixing. The present invention does not further limit the specific conditions of ball milling mixing, as long as the powder raw material, binder, dispersant and solvent can be uniformly mixed.
[0030] Preferably, the solvent comprises water.
[0031] In the preparation method provided by the present invention, the use of dispersants and binders is to achieve uniform dispersion of materials in the slurry. The present invention does not specifically limit their dosage and types, as long as the purpose of uniform dispersion can be achieved.
[0032] Spray granulation can ensure the uniform dispersion of various materials in the granulation powder, and controlling the water content of the granulation powder can enhance the plasticity of the granulation powder, which is convenient for subsequent molding.
[0033] Preferably, the water content of the granulated powder obtained by the spray granulation is 0.4wt% to 0.6wt%, for example, 0.4wt%, 0.5wt% or 0.6wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Preferably, the granulated powder obtained by the spray granulation can pass through a sieve with a first mesh size, but cannot pass through a sieve with a second mesh size.
[0035] The first mesh number is 50 meshes to 80 meshes, and the second mesh number is 270 meshes to 325 meshes.
[0036] If the particle size of the granulation powder is too large, it will easily lead to a large number of pores in the ZTA ceramic material; if the particle size of the granulation powder is too small, it will cause the ZTA ceramic material to crack and deform. In order to make the obtained ZTA ceramic material have good mechanical properties, the granulation powder needs to be able to pass through the first mesh sieve and not pass through the second mesh sieve.
[0037] Among them, the first mesh number is 50 mesh to 80 mesh, for example, it can be 50 mesh, 55 mesh, 60 mesh, 65 mesh, 70 mesh, 75 mesh or 80 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] The second mesh number is 270 mesh to 325 mesh, for example, it can be 270 mesh, 280 mesh, 300 mesh, 310 mesh or 325 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] Preferably, the preparation method further comprises aging after spray granulation and before molding.
[0040] Preferably, the aging time is more than 18 hours, for example, it can be 18 hours, 20 hours, 21 hours, 24 hours or 25 hours, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, the unidirectional pressure for molding is 150 MPa to 300 MPa, for example, 150 MPa, 180 MPa, 200 MPa, 250 MPa, 280 MPa or 300 MPa, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0042] The molding can be stable within this pressure range, thus improving the molding effect.
[0043] In the present invention, the heating rate during sintering affects the cracking problem of the obtained ceramic material. Therefore, selecting a suitable heating rate can avoid cracking generated during the preparation process.
[0044] Preferably, the sintering heating rate does not exceed 4°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min or 4°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] Preferably, the sintering temperature is 1520°C to 1650°C, for example, 1520°C, 1550°C, 1580°C, 1600°C or 1650°C, but is not limited to the listed values, and other values within the numerical range not listed are also applicable.
[0046] Preferably, the sintering time is 2 h to 4 h, for example, 2 h, 2.5 h, 3 h, 3.5 h or 4 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0047] In a third aspect, the present invention provides a photovoltaic device, wherein the photovoltaic device comprises the ZTA ceramic material described in the first aspect, or comprises the ZTA ceramic material obtained by the preparation method described in the second aspect.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] Zirconia has the property of reversible crystal transformation at high temperature. During the preparation process of ZTA ceramic materials, the crystal transformation leads to the generation of space inside the ZTA ceramic materials. This part of the space can be used for thermal expansion of grains, thereby enhancing the thermal shock resistance of ZTA ceramic materials. Under high temperature conditions, monoclinic zirconia transforms into a tetragonal phase with better stability, thereby enhancing the high temperature performance of ZTA ceramic materials and making up for the defect that the performance of ceramic materials decreases at high temperatures. Tabular corundum can leave a large amount of space vacancies during the preparation process of ZTA ceramic materials, thereby further improving the thermal shock resistance of ceramic materials and making up for the defect that the price of zirconia is too high. Moreover, the use of inorganic oxides plays a role in inhibiting grain growth and can reduce the firing temperature, so that the ceramic materials meet the various requirements of photovoltaic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 : is the SEM picture of the ZTA ceramic material obtained in Example 1.
[0051] Figure 2 This is a SEM image of the plate-shaped corundum used in Example 1. DETAILED DESCRIPTION
[0052] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0053] Example 1
[0054] This embodiment provides a ZTA ceramic material. The powder raw material of the ZTA ceramic material includes 75wt% of α-Al 2 O 3 , 5wt% monoclinic zirconia, 11wt% yttrium-stabilized tetragonal zirconia (5% yttrium oxide by mole), 5wt% plate-like corundum (SEM image as shown in Figure 2 As shown), 1wt% SiO 2 、1wt% MgO、1wt% Y 2 O 3 and 1 wt% CaO;
[0055] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0056] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0057] The preparation method of the ZTA ceramic material in this embodiment includes the following steps:
[0058] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0059] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0060] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0061] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0062] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0063] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0064] (4) The formed blank is heated to 1520° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the ZTA ceramic material.
[0065] The SEM image of the ZTA ceramic material obtained in this example is as follows Figure 1 shown.
[0066] Example 2
[0067] This embodiment provides a ZTA ceramic material. The powder raw material of the ZTA ceramic material includes 75wt% of α-Al 2 O 3 , 8wt% monoclinic zirconia, 8wt% yttrium-stabilized tetragonal zirconia (5% yttrium oxide by mole), 5wt% plate-like corundum, 1wt% SiO 2 、1wt% MgO、1wt% Y 2 O 3 and 1 wt% CaO;
[0068] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0069] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0070] The preparation method of the ZTA ceramic material in this embodiment includes the following steps:
[0071] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0072] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0073] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0074] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0075] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0076] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0077] (4) The formed blank is heated to 1520° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the ZTA ceramic material.
[0078] Example 3
[0079] This embodiment provides a ZTA ceramic material. The powder raw material of the ZTA ceramic material includes 75wt% of α-Al 2 O 3 , 11wt% monoclinic zirconia, 5wt% yttrium-stabilized tetragonal zirconia (5% yttrium oxide by mole), 5wt% plate-like corundum, 1wt% SiO 2 、1wt% MgO、1wt% Y 2 O 3 and 1 wt% CaO;
[0080] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0081] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0082] The preparation method of the ZTA ceramic material in this embodiment includes the following steps:
[0083] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0084] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0085] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0086] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0087] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0088] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0089] (4) The formed blank is heated to 1520° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the ZTA ceramic material.
[0090] Example 4
[0091] This embodiment provides a ZTA ceramic material. The powder raw material of the ZTA ceramic material includes 79wt% of α-Al 2 O 3 , 11wt% monoclinic zirconia, 5wt% plate-like corundum, 2wt% SiO 2 、1wt% MgO、1wt% Y 2 O 3 and 1 wt% CaO;
[0092] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0093] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0094] The preparation method of the ZTA ceramic material in this embodiment includes the following steps:
[0095] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0096] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0097] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0098] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0099] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0100] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a mold release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 180 MPa is applied for molding;
[0101] (4) The formed blank is heated to 1560° C. at a rate of 4° C. / min in a high temperature furnace and pressurelessly sintered for 3 h to obtain the ZTA ceramic material.
[0102] Example 5
[0103] This embodiment provides a ZTA ceramic material. The powder raw material of the ZTA ceramic material includes 79wt% of α-Al 2 O 3 , 11wt% yttrium-stabilized tetragonal zirconia (5% yttrium oxide by mole), 5wt% plate-like corundum, 2wt% SiO 2 、1wt% MgO、1wt% Y 2 O 3 and 1 wt% CaO;
[0104] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0105] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0106] The preparation method of the ZTA ceramic material in this embodiment includes the following steps:
[0107] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0108] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0109] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0110] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0111] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0112] (3) In order to facilitate subsequent separation from the mold, the granulated powder was uniformly mixed with a mold release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 210 MPa was applied for molding;
[0113] (4) The formed blank is heated to 1580° C. at a rate of 4° C. / min in a high temperature furnace and pressurelessly sintered for 4 h to obtain the ZTA ceramic material.
[0114] Example 6
[0115] This embodiment provides a ZTA ceramic material. The powder raw material of the ZTA ceramic material includes 75wt% of α-Al 2 O 3 , 11wt% yttrium-stabilized tetragonal zirconia (5% yttrium oxide by mole), 10wt% plate-like corundum, 1wt% SiO 2 、1wt% MgO、1wt% Y 2 O 3 and 1 wt% CaO;
[0116] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0117] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0118] The preparation method of the ZTA ceramic material in this embodiment includes the following steps:
[0119] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0120] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0121] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0122] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0123] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 50-mesh sieve but cannot pass through a 270-mesh sieve; the granulated powder has a moisture content of 0.4 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0124] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0125] (4) The formed blank is heated to 1650° C. at a rate of 4° C. / min in a high temperature furnace and pressurelessly sintered for 4 h to obtain the ZTA ceramic material.
[0126] Example 7
[0127] This embodiment provides a ZTA ceramic material. The powder raw material of the ZTA ceramic material includes 75wt% of α-Al 2 O 3 , 5wt% monoclinic zirconia, 16wt% plate-like corundum, 1wt% SiO 2 、1wt% MgO、1wt% Y 2 O 3 and 1 wt% CaO;
[0128] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0129] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0130] The preparation method of the ZTA ceramic material in this embodiment includes the following steps:
[0131] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0132] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0133] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0134] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0135] (2) spray granulation of the slurry to obtain granulated powder that can pass through an 80-mesh sieve but cannot pass through a 325-mesh sieve; the moisture content of the granulated powder is 0.6 wt %, and then the granulated powder is aged for 18 hours to make the moisture in the granulated powder evenly distributed;
[0136] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 300 MPa is applied for molding;
[0137] (4) The formed blank is heated to 1600° C. at a rate of 4° C. / min in a high temperature furnace and pressurelessly sintered for 3 h to obtain the ZTA ceramic material.
[0138] Example 8
[0139] The present embodiment provides a ZTA ceramic material. In terms of mass percentage, the powder raw materials of the ZTA ceramic material include 21wt% of α-Al2O3, 39wt% of monoclinic zirconia, 30wt% of yttrium-stabilized tetragonal zirconia (5% molar percentage of yttrium oxide), 5wt% of plate-like corundum, 2wt% of SiO2, 1wt% of MgO, 1wt% of Y2O3 and 1wt% of CaO.
[0140] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0141] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0142] The preparation method of the ZTA ceramic material in this embodiment includes the following steps:
[0143] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0144] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0145] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0146] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0147] (2) spray granulation of the slurry to obtain granulated powder that can pass through an 80-mesh sieve but cannot pass through a 325-mesh sieve; the moisture content of the granulated powder is 0.6 wt %, and then the granulated powder is aged for 18 hours to make the moisture in the granulated powder evenly distributed;
[0148] (3) In order to facilitate subsequent separation from the mold, the granulated powder was uniformly mixed with a mold release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 210 MPa was applied for molding;
[0149] (4) The formed blank is heated to 1520° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the ZTA ceramic material.
[0150] Example 9
[0151] The present embodiment provides a ZTA ceramic material. In terms of mass percentage, the powder raw materials of the ZTA ceramic material include 21wt% of α-Al2O3, 29wt% of monoclinic zirconia, 40wt% of yttrium-stabilized tetragonal zirconia (5% molar percentage of yttrium oxide), 5wt% of plate-like corundum, 2wt% of SiO2, 1wt% of MgO, 1wt% of Y2O3 and 1wt% of CaO.
[0152] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0153] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0154] The preparation method of the ZTA ceramic material in this embodiment includes the following steps:
[0155] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0156] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0157] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0158] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0159] (2) spray granulation of the slurry to obtain granulated powder that can pass through an 80-mesh sieve but cannot pass through a 325-mesh sieve; the moisture content of the granulated powder is 0.6 wt %, and then the granulated powder is aged for 18 hours to make the moisture in the granulated powder evenly distributed;
[0160] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a mold release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 240 MPa is applied for molding;
[0161] (4) The formed blank is heated to 1520° C. at a rate of 4° C. / min in a high temperature furnace and pressureless sintered for 4 h to obtain the ZTA ceramic material.
[0162] Example 10
[0163] The present embodiment provides a ZTA ceramic material. In terms of mass percentage, the powder raw materials of the ZTA ceramic material include 50wt% of α-Al2O3, 5wt% of monoclinic zirconia, 21wt% of yttrium-stabilized tetragonal zirconia (5% yttrium oxide by mole), 21wt% of plate-like corundum, 1wt% of SiO2, 1wt% of MgO and 1wt% of CaO.
[0164] Among them, the aspect ratio of tabular corundum is 10:1, and the average particle size is 1μm;
[0165] Among them, the average particle size of monoclinic zirconia and yttrium-stabilized tetragonal zirconia is 1 μm;
[0166] The preparation method of the ZTA ceramic material in this embodiment includes the following steps:
[0167] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0168] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0169] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0170] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0171] (2) spray granulation of the slurry to obtain granulated powder that can pass through an 80-mesh sieve but cannot pass through a 325-mesh sieve; the moisture content of the granulated powder is 0.6 wt %, and then the granulated powder is aged for 18 hours to make the moisture in the granulated powder evenly distributed;
[0172] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0173] (4) The formed blank is heated to 1650° C. at a rate of 4° C. / min in a high temperature furnace and pressurelessly sintered for 2 h to obtain the ZTA ceramic material.
[0174] Embodiment 11
[0175] This embodiment provides a ZTA ceramic material, which is the same as that of Embodiment 1 except that the sintering temperature is 1600° C.
[0176] Example 12
[0177] This embodiment provides a ZTA ceramic material, which is the same as that of Embodiment 1 except that the sintering temperature is 1650° C.
[0178] Embodiment 13
[0179] This embodiment provides a ZTA ceramic material, which is the same as that of Embodiment 1 except that the aspect ratio of the plate-shaped corundum is 8:1.
[0180] Embodiment 14
[0181] This embodiment provides a ZTA ceramic material, which is the same as that of Embodiment 1 except that the aspect ratio of the plate-shaped corundum is 12:1.
[0182] Comparative Example 1
[0183] This comparative example provides a ceramic material, in terms of mass percentage, the powder raw material of the ceramic material includes 95wt% of α-Al 2 O 3 and 5wt% SiO 2 ;
[0184] The preparation method of the ceramic material in this comparative example comprises the following steps:
[0185] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0186] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0187] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0188] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0189] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0190] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0191] (4) The formed blank is heated to 1600° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the ceramic material.
[0192] Comparative Example 2
[0193] This comparative example provides a ceramic material, in terms of mass percentage, the powder raw material of the ceramic material includes 65wt% of α-Al 2 O 3 and 35wt% SiO 2 ;
[0194] The preparation method of the ceramic material in this comparative example comprises the following steps:
[0195] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0196] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0197] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0198] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0199] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0200] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0201] (4) The formed blank is heated to 1600° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the ceramic material.
[0202] Comparative Example 3
[0203] This comparative example provides a ceramic material, in which the powder raw materials of the ceramic material include 96wt% SiC, 1.4wt% AlN, 1.6wt% Al 2 O 3 and 1wt% Y 2 O 3 ;
[0204] The preparation method of the ceramic material in this comparative example comprises the following steps:
[0205] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0206] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0207] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0208] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0209] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0210] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0211] (4) The formed blank is heated to 2200° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the ceramic material.
[0212] Comparative Example 4
[0213] This comparative example provides a ceramic material, in terms of mass percentage, the powder raw material of the ceramic material includes 79wt% of Al 2 O 3 and 21wt% Y 2 O 3 ;
[0214] The preparation method of the ceramic material in this comparative example comprises the following steps:
[0215] (1) ball milling the mixed powder raw materials, binder, dispersant and solvent for 48 hours to obtain a uniformly mixed slurry;
[0216] The binder is polyvinyl alcohol (PVA, Anhui Wanwei, 20-88), and the amount is 0.5wt% of the powder raw material;
[0217] The dispersant was polyammonium acrylate (PAA, Wuhan Chenyu, CYD-66), and the dosage was 2.5wt% of the powder raw material;
[0218] The solvent is water, and the amount used is 50wt% of the powder raw material;
[0219] (2) spray granulation of the slurry to obtain granulated powder that can pass through a 60-mesh sieve but cannot pass through a 300-mesh sieve; the granulated powder has a moisture content of 0.5 wt %, and then aged for 18 h to make the moisture in the granulated powder evenly distributed;
[0220] (3) In order to facilitate subsequent separation from the mold, the granulated powder is uniformly mixed with a release agent (magnesium stearate, Qinuo, YZSM) at 0.3% by mass of the granulated powder, and then a uniaxial pressure of 150 MPa is applied for molding;
[0221] (4) The formed blank is heated to 1600° C. at a rate of 4° C. / min in a high temperature furnace and subjected to pressureless sintering for 2 h to obtain the ceramic material.
[0222] Performance Characterization
[0223] The density, 25° C. flexural strength, high temperature flexural strength and thermal shock resistance of the ZTA ceramic material obtained in the above embodiment and the ceramic material obtained in the comparative example were measured, and the results are shown in Table 1.
[0224] Among them, the density test method is GB / T 25995-2010 fine ceramic density and apparent porosity test method; the method described in GB / T 3001-2017 is used to test the room temperature flexural strength of refractory materials, the method described in GB / T3002-2017 is used to test the high temperature (1100℃) flexural strength of refractory materials, and the method described in GB / T 30873-2014 is used to test the thermal shock resistance of refractory materials.
[0225] Table 1
[0226]
[0227]
[0228] In summary, the present invention utilizes the reversible crystal transformation property of zirconium oxide at high temperature. During the preparation process of ZTA ceramic material, the crystal transformation leads to the generation of space inside the ZTA ceramic material, and this part of the space can be used for thermal expansion of grains, thereby enhancing the thermal shock resistance of the ZTA ceramic material. Under high temperature conditions, the monoclinic zirconium oxide is transformed into a tetragonal phase with better stability, thereby enhancing the high temperature performance of the ZTA ceramic material and compensating for the defect that the performance of the ceramic material decreases at high temperature. Tabular corundum can leave a large amount of space vacancies during the preparation process of the ZTA ceramic material, thereby further improving the thermal shock resistance of the ceramic material and compensating for the defect that the price of zirconium oxide is too high. Moreover, the use of inorganic oxides plays a role in inhibiting grain growth and can reduce the firing temperature, so that the ceramic material meets the various requirements of photovoltaic devices.
[0229] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A ZTA ceramic material, characterized in that: In terms of mass percentage, the powder raw materials of the ZTA ceramic material include 5wt% to 69wt% of zirconium oxide, 5wt% to 21wt% of plate-like corundum, 3wt% to 5wt% of inorganic oxides and 21wt% to 79wt% of aluminum oxide.
2. The ZTA ceramic material according to claim 1, characterized in that: Taking the maximum length of the plate-shaped corundum as the length and the thickness of the plate-shaped corundum as the height, the aspect ratio of the plate-shaped corundum is 8:1 to 12:
1.
3. The ZTA ceramic material according to claim 1 or 2, characterized in that: The zirconium oxide includes monoclinic zirconium oxide and yttrium-stabilized tetragonal zirconium oxide; Preferably, in the raw materials for preparing the ZTA ceramic material, the amount of monoclinic zirconium oxide is lower than the amount of yttrium-stabilized tetragonal zirconia; Preferably, the powder raw material of the ZTA ceramic material includes, by mass percentage, 5wt% to 39wt% of monoclinic zirconium oxide and 5wt% to 40wt% of yttrium-stabilized tetragonal zirconia.
4. The ZTA ceramic material according to any one of claims 1 to 3, characterized in that: The inorganic oxide includes any one of silicon oxide, magnesium oxide, yttrium oxide or calcium oxide, or a combination of at least two thereof, preferably a combination of silicon oxide, magnesium oxide, yttrium oxide and calcium oxide; Preferably, the mass ratio of the silicon oxide to the magnesium oxide is 1:1 to 1:3, the mass ratio of the silicon oxide to the yttrium oxide is 1:1 to 1:3, and the mass ratio of the silicon oxide to the calcium oxide is 1:1 to 1:
3.
5. A method for preparing the ZTA ceramic material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The powder raw material, binder, dispersant and solvent are uniformly mixed, the obtained slurry is sprayed and granulated, and then formed and sintered to obtain the ZTA ceramic material.
6. The preparation method according to claim 5, characterized in that: The water content of the granulated powder obtained by the spray granulation is 0.4wt% to 0.6wt%; Preferably, the granulated powder obtained by the spray granulation can pass through a first mesh sieve and cannot pass through a second mesh sieve; The first mesh number is 50 meshes to 80 meshes, and the second mesh number is 270 meshes to 325 meshes.
7. The preparation method according to claim 5 or 6, characterized in that: The preparation method also includes aging after spray granulation and before molding; Preferably, the aging time is more than 18 hours.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The one-way pressure of the molding is 150 MPa to 300 MPa.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The heating rate of the sintering does not exceed 4°C / min; Preferably, the sintering temperature is 1520°C to 1650°C; Preferably, the sintering time is 2 h to 4 h.
10. A photovoltaic device, characterized in that: The photovoltaic device comprises the ZTA ceramic material according to any one of claims 1 to 4, or comprises the ZTA ceramic material obtained by the preparation method according to any one of claims 5 to 9.
Citation Information
Patent Citations
98 aluminum oxide photovoltaic insulating ceramic
CN117602956A
Preparation method of high-wear-resistance ZTA ceramic material
CN117776751A
Low-heat-storage mullite sagger for sintering high-purity alumina powder and preparation method of low-heat-storage mullite sagger
CN118026658A
Alumina ceramic ring having high thermal shock resistance and used for polycrystalline silicon reduction furnace as well as preparation method
CN104788083A
Preparation method and equipment of zirconia metering nozzle
CN104876596A
Cited By
Preparation method of zirconium oxide toughened aluminum oxide grinding ball
CN122355691A